THE EFFICIENCY OF THE HIGHER EDUCATION FUND AND ITS IMPACT ON THE EDUCATIONAL PROCESS ANALYTICAL STUDY OF THE HIGHER EDUCATION FUND AT THE COLLEGE OF ADMINISTRATION AND ECONOMICS - UNIVERSITY OF KARBALA (2014-2023) - Hashim jabbar hussein; Abbas Abdulaali kareem AlAbboodi; Ali Ahmed Faris (Scholar Express Journals, 2025)
The research seeks to measure the impact of the efficiency of the Higher Education Fund on the educational process, as improving the efficiency of the Higher Education Fund can lead to enhancing available resources and improving academic performance. The research community may be from the colleges of the University of Karbala, and the research sample represented by the College of Administration and Economics was selected for the period 2014-2023. The data envelope, data stability test (Extended Dickey-Fuller (developed)), Pearson correlation and simple effect were used through a set of statistical programs (EMS V. 1.3, Eviews Vs. 12, SPSS V. 25). The research reached a set of results, the most important of which is that there is a statistically significant impact of the efficiency of the Higher Education Fund in improving the educational process. In light of this, the research came out with a number of recommendations, the most important of which is that the college administration should benefit from these results to develop strategies aimed at enhancing the efficiency of the Higher Education Fund, which may contribute to improving the educational performance of the institution
Keywords: Higher Education Fund efficiency; DEA; educational process